2023
DOI: 10.1111/fcp.12865
|View full text |Cite
|
Sign up to set email alerts
|

Gemfibrozil, a lipid‐lowering drug, improves hepatorenal damages in a mouse model of aging

Abstract: Gemfibrozil (GFZ) is a medication of the fibrate category with agonistic effects on peroxisome proliferator‐activated receptor‐α (PPAR‐α) and is effective for hypertriglyceridemia and mixed dyslipidemia. This agent also has anti‐inflammatory and antioxidant properties. The current study investigated the effects of GFZ on hepatorenal damages in a D‐galactose (D‐gal)‐induced aging model. We used 28 male mice, which were equally and randomly divided into four groups as follows: normal, D‐gal (150 mg/kg/day; intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Similar ndings were observed in ischemia reperfusion AKI model (Kaur et al 2021) and renal brosis model (Xu et al 2020). Adding to that, gem brozil showed the same bene cial effect on kidney function in D-galactose aging model (Hakimizadeh et al 2023) and in obese Dahl salt sensitive rats (Shields et al 2020). Gem brozil bene ts exceeded lipid lowering effects, leading to lower glomerular damage, decrease in proteinuria level, lower blood pressure and improved kidney function.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similar ndings were observed in ischemia reperfusion AKI model (Kaur et al 2021) and renal brosis model (Xu et al 2020). Adding to that, gem brozil showed the same bene cial effect on kidney function in D-galactose aging model (Hakimizadeh et al 2023) and in obese Dahl salt sensitive rats (Shields et al 2020). Gem brozil bene ts exceeded lipid lowering effects, leading to lower glomerular damage, decrease in proteinuria level, lower blood pressure and improved kidney function.…”
Section: Discussionmentioning
confidence: 92%
“…Beyond lipid lowering effect feno brate presented antiproliferative, anti-in ammatory and antioxidative properties as well as lowered blood pressure in animals models of diabetic nephropathy (Zhao and Li 2008). Similarly, gem brozil was shown to improve organ function and oxidative stress level, distinct from hypolipidemic effect in the animal model of aging (Hakimizadeh et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These findings agree with a previous study that confirmed that gemfibrozil administration increases relative and absolute liver weights in male rats, 31 and agree with study done by Liu and his colleagues, which stated that liver index increased by 65% after gemfibrozil treatment in rats when compared with the control group 32 and agree with previously published research that provide evidence for the potential therapeutic of gemfibrozil in clinical practice for mitigating the hepatic renal damages of aging in D-galactose aged mice. 33 Possible explanation for the effect of gemfibrozil is through its role in apoptotic pathways. In previous studies, it had been demonstrated that oxidative stress might lead to apoptosis, which was the main cause of many types of organ damages.…”
Section: Discussionmentioning
confidence: 99%
“…Seven days after arrival, the animals were randomly divided into six experimental groups (7 animals/group). The control group received standard drinking water (10 mL/kg) (Hakimizadeh et al, 2023 ), while all the other groups received d ‐gal (Sigma‐Aldrich, Darmstadt, Germany) freshly dissolved in drinking water (10 mL/kg) for oral administration at a dose of 500 mg/kg/day, for 6 weeks (Hakimizadeh et al, 2021 ). Vitamin D (Vit D, Sigma Aldrich, USA) was dissolved in propylene glycol as a vehicle (Sigma Aldrich, USA).…”
Section: Methodsmentioning
confidence: 99%